(untitled) (Research, Society and Development, 2021)
Introduction: The Brazilian economic crisis experienced in the second decade of the 21st century required changes in the labor market due to unemployment. Objective: To analyze the serious work accidents that occurred among workers with and without employment relationship. Methodology: Cross-sectional observational study with data from the Employee’s Report of Injury Form, which reported major injuries involving upper limbs from 2016 to 2017. Data were analyzed using Pearson’s chi-square. Results: 370 compulsory reporting forms were analyzed. There was a high prevalence of major injuries among construction and carpentry men. It was also observed a higher prevalence of workers without employment relationship, who said they had less difficulty in operating the equipment that caused the accident but participated less in training and use activities of personal protective equipment. Conclusion: The moment of economic crisis and, consequently in employment, has generated a growth of unrelated workers, who are more exposed to serious accidents at work. This group of workers will demand more action from public services to develop training and incentive actions to use protection at work.